ChemInform Abstract: Cross‐Coupling of Heteroarenes by C—H Functionalization: Recent Progress Towards Direct Arylation and Heteroarylation Reactions Involving Heteroarenes Containing One Heteroatom. Issue 19 (13th May 2014) - Rossi, Renzo; Bellina, Fabio; Lessi, Marco; Manzini, Chiara
Abstract Review: results obtained from January 2009 to February 2013 in the area of transition metal‐catalyzed title arylation reactions; 430 refs.